Paeonol enhances macrophage phagocytic function by modulating lipid metabolism through the P53-TREM2 axis - Miao, Jifei; Liu, Xiaoming; Liao, Yuanpin; Li, Yiwen; Kuang, Yingyan; Zheng, Juanxia; Li, Zigang; Lan, Jiao (Frontiers in Pharmacology, 2023)
The emerging concept of immunometabolism highlights the interplay between lipid metabolism and phagocytosis in macrophages. Triggering Receptor Expressed on Myeloid Cells 2 (TREM2) has been identified as an essential modulator of both lipid metabolism and phagocytic function in macrophages. This study aims to investigate the roles of P53 and TREM2 in regulating macrophage lipid metabolism and phagocytosis and to evaluate the potential therapeutic effects of paeonol on these processes. CRISPR-Cas9 was utilized to generate P53 and TREM2 knockout RAW264.7 cell lines. The dual-luciferase reporter gene assay was performed to assess the interaction between P53 and the TREM2 promoter. A series of functional assays were conducted to evaluate the impact of P53 and TREM2 on macrophage lipid metabolism and phagocytic function. The effects of Paeonol on these processes were also examined. We have previously reported that paeonol treatment significantly enhanced the phagocytic function of macrophages. However, the relationship between this phenomenon and the TREM2 and lipid metabolism is unclear. Our findings revealed that paeonol induces the accumulation of P53 in the nucleus. P53 acts as a transcription factor that upregulates the expression of TREM2, promoting macrophage lipid metabolism, metabolic activity, and phagocytic capacity. Additionally, dual-luciferase reporter gene assays confirmed the interaction between P53 and the TREM2 promoter. This study provides novel insights into the roles of P53 and TREM2 in regulating macrophage lipid metabolism and phagocytic function. Further research is warranted to explore the potential applications of Paeonol and to elucidate the molecular mechanisms underlying the observed effects.